Robots and reshoring: Evidence from Mexican local labor markets - Marius Faber (University of Basel, Center of Business and Economics (WWZ), 2018)
Robots in advanced economies have the potential to reduce employment in offshoring countries by fueling reshoring. Using robots instead of humans for production may reduce the relative cost of domestic production and, in turn, lower demand for imports from offshoring countries. I analyze the impact of robots on employment in an offshoring country, using data from Mexican local labor markets between 1990 and 2015. A recent literature shows that the effect of robots on local employment can be estimated by regressing the change in employment on exposure to domestic robots in local labor markets. I similarly construct a measure of exposure to foreign robots, assuming that the share of US robots competing with Mexican labor is proportional to that industry's initial reliance on Mexican imports. Using robot penetration in the rest of the world (i.e., neither in Mexico nor in the US) as an instrument for domestic and foreign robotization, I show that the use of robots in the US has a robust and sizable, negative impact on employment in Mexico by reducing exports to the US. The effect is not driven by pre-existing trends, the automotive industry or migration patterns. It is strongest for low-skilled machine operators and technicians in highly robotized manufacturing industries as well as high-skilled managers and professionals in the service industry.
Keywords: 330